The Relations of Islamic Republic of Iran with Muslim Brotherhood; From Strategic Alignment to Ideological Competition - Mostafa Ghasemi; mohammad ali basiri; Enayatollah Yazdani (Faṣlnāmah-i Pizhūhish/hā-yi Rāhburdī-i Siyāsat, 2020)
The Islamic Republic of Iran has experienced three levels of movement-movement, government-movement, and government-government relationship with Muslim Brotherhood. Although it is believed that Muslim Brotherhood have established good relationships with the Islamic Republic after its coming into power, but in the regional affairs stood against the policies of Islamic Republic of Iran. Many political and academic societies of Iran, with emphasizing on the development of relations, recommend a change in the strategy of supporting Muslim Brotherhood in Sunni world. The present paper uses library method along with a descriptive-analytical approach in order to answer the question that: at which level should the most suitable level of relations and Strategy between Islamic Republic and the Muslim Brotherhood be defined? Here is the research finding: Findings show that due to the ideological nature of the political system resulting from the Shiite movement in Iran and the Sunni movement of the Muslim Brotherhood and its rivalries and frictions, the most desirable level of relations between the Islamic Republic and the Muslim Brotherhood should be defined and pursued at the "government-movement" level" and based on the "state refusal, movement continuation" strategy.